Evaluation of the IP-10 mRNA release assay for diagnosis of TB in HIV-infected individuals - Tang, Yang; Yu, Yanhua; Wang, Quan; Wen, Zilu; Song, Ruixue; Li, Yu; Zhou, Yingquan; Ma, Ruiying; Jia, Hongyan; Bai, Shaoli; Abdulsalam, Harimulati; Du, Boping; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
HIV-infected individuals are susceptible to Mycobacterium tuberculosis (M.tb) infection and are at high risk of developing active tuberculosis (TB). Interferon-gamma release assays (IGRAs) are auxiliary tools in diagnosis of TB. However, the performance of IGRAs in HIV-infected individuals is suboptimal, which limits clinical application. Interferon-inducible protein 10 (IP-10) is an alternative biomarker for identifying M.tb infection due to its high expression after stimulation with M.tb antigens. However, whether IP-10 mRNA constitutes a target for the diagnosis of TB in HIV-infected individuals is unknown. Thus, we prospectively enrolled HIV-infected patients with suspected active TB from five hospitals between May 2021 and May 2022, and performed the IGRA test (QFT-GIT) alongside the IP-10 mRNA release assay on peripheral blood. Of the 216 participants, 152 TB patients and 48 non-TB patients with a conclusive diagnosis were included in the final analysis. The number of indeterminate results of IP-10 mRNA release assay (13/200, 6.5%) was significantly lower than that of the QFT-GIT test (42/200, 21.0%) (P = 0.000026). IP-10 mRNA release assay had a sensitivity of 65.3% (95%CI 55.9% – 73.8%) and a specificity of 74.2% (95%CI 55.4% – 88.1%), respectively; while the QFT-GIT test had a sensitivity of 43.2% (95%CI 34.1% – 52.7%) and a specificity of 87.1% (95%CI 70.2% – 96.4%), respectively. The sensitivity of the IP-10 mRNA release assay was significantly higher than that of QFT-GIT test (P = 0.00062), while no significant difference was detected between the specificities of these two tests (P = 0.198). The IP-10 mRNA release assay showed a lower dependence on CD4+ T cells than that of QFT-GIT test. This was evidenced by the fact that the QFT-GIT test had a higher number of indeterminate results and a lower sensitivity when the CD4+ T cells counts were decreased (P < 0.05), while no significant difference in the number of indeterminate results and sensitivity were observed for the IP-10 mRNA release assay among HIV-infected individuals with varied CD4+T cells counts (P > 0.05). Therefore, our study suggested that M.tb specific IP-10 mRNA is a better biomarker for diagnosis of TB in HIV-infected individuals.